A strategy for the efficient construction of anti-PD1-based bispecific antibodies with desired IgG-like properties - Jie Zhao; Liangfeng Jiang; Haodong Yang; Lan Deng; Xiaoqing Meng; Jian Ding; Sixing Yang; Le Zhao; Wei Xu; Xiaolong Wang; Zhenping Zhu; Haomin Huang (Taylor & Francis Group, 2022)
Targeting PD1/PDL1 with blocking antibodies for cancer therapy has shown promising benefits in the clinic, but only approximately 20-30% of patients develop durable clinical responses to the treatment. Bispecific antibodies (BsAbs) that combine PD1/PDL1 blockade with the modulation of another immune checkpoint target may have greater potential to enhance immune checkpoint blockade therapy. In this study, we identified an anti-PD1 monoclonal antibody, 609A, whose heavy chain can pair with a variety of light chains from different antibodies while maintaining its PD1 binding/blocking activity. Taking advantage of this property and using a linear F(ab')2 format, we successfully produced a series of tetravalent IgG-like BsAbs that simultaneously target PD1 and other immune checkpoint targets, including PDL1 and CTLA4. The BsAbs exhibited superior bioactivities in vitro and in vivo compared to their respective parental mAbs. Importantly, the BsAbs demonstrated the desired IgG-like physicochemical properties in terms of high-level expression, ease of purification to homogeneity, good stability and in vivo pharmacokinetics. In summary, we describe a novel and flexible plug-and-play platform to engineer IgG-like BsAbs with excellent development potential for clinical applications.